2023
DOI: 10.3389/fnut.2023.1093761
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the metabolic profiling of Polygonati Rhizoma fermented by Lactiplantibacillus plantarum under aerobic and anaerobic conditions using a UHPLC-QE-MS/MS system

Abstract: IntroductionPolygonati Rhizoma is a multi-purpose food with medicinal uses. Fermentation of Polygonati Rhizoma by lactic acid bacteria could provide new insights into the development of Polygonati Rhizoma products.MethodsIn this study, Lactiplantibacillus plantarum was fermented with Polygonati Rhizoma extracts in a bioreactor under aerobic and anaerobic conditions with pH and DO real-time detection. Metabolic profiling was determined by UHPLC-QE-MS/MS system. Principal component analysis and orthogonal partia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…( Li et al, 2021 , Yu et al, 2023 ) used Lactobacillus plantarum to ferment blueberry juice, and the results showed that fermentation significantly increased the clearance rates of DPPH and superoxide anion free radicals, and had an alleviating effect on the oxidative damage of Caco-2 cells. ( Wang et al, 2023 , Aleman et al, 2023 ) studied the effects of fermentation of six commercial lactic acid bacteria on the active phytochemicals, antioxidant activity and flavor in wolfberry juice, and the results showed that the antioxidant activity based on DPPH, ABTS and FRAP methods according to LAB fermentation has been significantly improved. The improvement of antioxidant activity of wolfberry juice is the synergistic effect of various antioxidants in wolfberry juice, such as phenolic acids, flavonoids and vitamins.…”
Section: Functional Activities Of Fermented Fruit and Vegetable Juicementioning
confidence: 99%
“…( Li et al, 2021 , Yu et al, 2023 ) used Lactobacillus plantarum to ferment blueberry juice, and the results showed that fermentation significantly increased the clearance rates of DPPH and superoxide anion free radicals, and had an alleviating effect on the oxidative damage of Caco-2 cells. ( Wang et al, 2023 , Aleman et al, 2023 ) studied the effects of fermentation of six commercial lactic acid bacteria on the active phytochemicals, antioxidant activity and flavor in wolfberry juice, and the results showed that the antioxidant activity based on DPPH, ABTS and FRAP methods according to LAB fermentation has been significantly improved. The improvement of antioxidant activity of wolfberry juice is the synergistic effect of various antioxidants in wolfberry juice, such as phenolic acids, flavonoids and vitamins.…”
Section: Functional Activities Of Fermented Fruit and Vegetable Juicementioning
confidence: 99%
“…Metabolomics-based profiling was done using a UPLC-ESI-Q-Orbitrap-MS/MS system (UHPLC, Shimadzu Nexera X2 LC-30AD, Shimadzu, Japan) coupled with Q-Exactive Plus (Thermo Scientific, San Jose, USA) [32] . For hydrophilic interaction liquid chromatography separation, samples were analyzed using a 2.1 mm*100 mm ACQUIY UPLC BEH Amide 1.7 μm column (Waters, Ireland).…”
Section: Uhplc-ms/ms Analysismentioning
confidence: 99%
“…The metabolites of Polygonati Rhizoma fermented with Lactiplantibacillus plantarum were mainly involved in pathways of ABC transport and amino acid biosynthesis [58]. The levels of several compounds in Polygonati Rhizoma such as L-arginine, L-leucine, L-lysine, L-aspartic acid, citrate, carnitine, inosine, betaine and thiamine were significantly increased during L. plantarum fermentation, and these metabolites could significantly enhance food flavor [58].…”
Section: Other Functional Componentsmentioning
confidence: 99%
“…The metabolites of Polygonati Rhizoma fermented with Lactiplantibacillus plantarum were mainly involved in pathways of ABC transport and amino acid biosynthesis [58]. The levels of several compounds in Polygonati Rhizoma such as L-arginine, L-leucine, L-lysine, L-aspartic acid, citrate, carnitine, inosine, betaine and thiamine were significantly increased during L. plantarum fermentation, and these metabolites could significantly enhance food flavor [58]. Compared with anaerobic fermentation, aerobic conditions could significantly enhance the activities of branched-chain amino acid transaminase, isocitrate dehydrogenase, and glutamate dehydrogenase, which ultimately led to a significant rise in the levels of valine, isoleucine, and glutamate [58].…”
Section: Other Functional Componentsmentioning
confidence: 99%